Pemahaman Modul dan Implementasi Transaksi Akuntansi Pada Software PT. Hashmicro Solusi Indonesia - Wulandary, Sandra Dwina; Karmudiandri, Arwina; Marlinah, Aan; Rudyanto, Astrid (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2023)
The internship process at PT Hashmicro Solusi Indonesia which is carried out through MBKM activities can create flexible learning in higher education. Internship program activities can also build an innovative learning culture and provide the knowledge and skills needed by students in facing the competitive world of work in accordance with the times, technological advances, and societal dynamics. The internship program activities carried out at PT Hashmicro Solusi Indonesia's Accounting Specialist division are focused on carrying out activities to understand Hashmicro's ERP modules related to accounting and financial reports, handling client issues, conducting meetings with clients related to discussing issues, analyzing the implementation of transactions related to accounting on Hashmicro ERP Software, making work reports in PDF document form on accounting transaction work practices, and presenting work results to mentors on accounting transaction work practices. Internship program activities produce several things such as knowledge, attitudes, general skills, and special skills. Knowledge of software such as functions, usability, and how to operate menus and submenus. Attitudes acquired regarding how to serve and deal with clients properly and correctly. General skills in terms of being able to work with teams, being able to think critically, and solving problems quickly and precisely. As well as special skills obtained such as being able to understand client accounting transactions and provide the desired output from the client from the Hashmicro ERP software.